1992
DOI: 10.1159/000147312
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Distribution of Non-Haem Iron in the Human Brain

Abstract: The detailed anatomical distribution of iron in the post-mortem human brain has been studied using Perl’s and Turnbull’s methods with the diaminobenzidine intensification procedure for the demonstration of non-haem Fe3+ and Fe2+ respectively. Attention to methodological procedures has revealed that even brief immersion of tissue in routinely used fixatives causes a reduction of staining intensity in areas of high iron content and, often, loss of staining in areas of low iron content. Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
144
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(171 citation statements)
references
References 26 publications
25
144
2
Order By: Relevance
“…In the cortex, regional variations in T 2 have been attributed to cortical variation in iron concentration, rather than to blood volume differences (43). Perl's iron stains of brain sections from a rhesus monkey (44) and humans (45,46) indicate a GM iron concentration that varies across cortical layers, with deeper layers having the highest iron concentration. Similarity with the MRI phase data are illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the cortex, regional variations in T 2 have been attributed to cortical variation in iron concentration, rather than to blood volume differences (43). Perl's iron stains of brain sections from a rhesus monkey (44) and humans (45,46) indicate a GM iron concentration that varies across cortical layers, with deeper layers having the highest iron concentration. Similarity with the MRI phase data are illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fe(III) and Fe(II), are extensively distributed throughout the brain, are especially highly concentrated in the diencephalon, basal ganglia, brain stem, and cerebellum, s i m i l a r t o p r e v i o u s o b s e r v a t i o n s f o r F e ( I I I ) i n various mammalian and human brains (Hill and Switzer, 1984;Connor et al, 1990;Morris et al, 1992;Gilissen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Progressive iron accumulation with age in specific brain regions has long been known in humans and other mammals (Hill and Switzer, 1984;Morris et al, 1992). Recent magnetic resonance imaging (MRI) studies of the human brain also demonstrated such increased iron accumulation with age in these brain regions (Drayer et al, 1986;Xu et al, 2008).…”
Section: Increased Nonheme Fe(iii) and Fe(ii) Accumulation With Agementioning
confidence: 99%
“…MRI can measure brain iron levels through the effect of iron on transverse relaxation rates (R 2 ) (Bartzokis et al, 1993;Bartzokis et al, 1994;Vymazal et al, 1996a;Yao et al, 2009). The bulk of brain iron is stored in ferritin molecules (Floyd and Carney, 1993;Morris et al, 1992) and an in vivo MRI method called field-dependent relaxation rate (R 2 ) increase (FDRI) can measure their iron content (Bartzokis et al, 1993;Bartzokis et al, 1994). Briefly, FDRI is the difference in measures of brain R 2 obtained with two different fieldstrength MRI instruments.…”
Section: Introductionmentioning
confidence: 99%